Health of International Migrant Workers During the COVID-19 Pandemic: A Scoping Review - Oliva-Arocas, Adriana; Benavente, Pierina; Ronda, Elena; Diaz, Esperanza (Frontiers in Public Health, 2022)
Background: The coronavirus pandemic and control measures adopted have had a disproportionate impact on workers, migrants being a group specifically affected but poorly studied. The present scoping review aims to describe the evidence published on the impact of the COVID-19 pandemic on the physical and mental health of migrant workers. Methods: Papers written in English covering physical and mental health among international migrant workers during the COVID-19 pandemic retrieved from six electronic databases searched on July 31st, 2021, were included. A total of 1096 references were extracted, of which 26 studies were finally included. Results: Most of the migrant populations studied were born in Asia (16 of 26) and Latin America (8 of 26) and were essential workers (15 of 26). Few studies described the length of stay in the host country (9 of 26), the legal status of the migrant population (6 of 26), or established comparison groups (7 of 26). Ten studies described COVID-19 outbreaks with high infection rates. Fourteen studies evaluated mental health (anxiety, depression, worries, fears, stress, and post-traumatic stress disorder). Three of the twenty-six studies presented collateral positive effects of the COVID-19 pandemic because of improved hygiene. Conclusion: There is a limited number of original publications related to the impact of the COVID-19 pandemic on the physical and mental health of migrant workers around the world. These publications are mainly focused on migrants born in Asian and Latin American countries. The physical, long-term impact of the COVID-19 pandemic is, so far, not been evaluated. The positive collateral effects of improving health care conditions for migrant workers should also be further investigated.